Urgency of Reduces Adoption Risk - Suyatmin Waskito Adi; Edy Purwo Saputro; Dewi Probowati Setyaningrum (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Research related to the adoption of e-filing is interesting to study because a number of previous studies have shown mixed results, so this is an interesting research gap. The purpose of this research is to examine the success factors of e-filing adoption using the TAM model involving respondents who have passed the taxation course with the observation setting in Solo involving 100 students. The research results corroborate the findings of a number of previous studies on the effect of benefit, convenience and risk on e-filing adoption. These results provide suggestions for stakeholders to disseminate information about the benefits and conveniences of e-filing, although on the other hand it is important to reduce all risk threats from e-filing.